Pengaruh Kepuasan Kompensasi terhadap Kinerja Karyawan dengan Disiplin Kerja sebagai Variabel Mediasi (Studi pada Karyawan PT Pura Unit Engineering) - Maulina, Salisa Nur; Djastuti, Indi (Diponegoro Journal of Management, 2024)
ABSTRACT This study aims to analyze and determine the effect of compensation satisfaction on employee performance through work discipline as an intervening variable at PT Pura Barutama Unit Engineering. The number of samples used in this study is 89 respondents which are permanent employees. Data was collected through the distribution of questionnaires and the hypothesis in this study were tested using the SEM-PLS (Structural Equation Modelling-Partial Least Square). The statistical test shows the results that compensation satisfaction variable have a significant positive effect on employee performance. In addition, it is also proven by this study that work discipline variable can mediate the relation between compensation satisfaction on employee performance.